Risk Factors For Hypertension In Pregnant Women - Febriyanti, Febriyanti; Anna Sari Dewi; Abdul Rahman (Sean Institute, 2024)
Hypertension is blood pressure more than 140/90 mmHg. Hypertension is a world problem that has hit the world. According to WHO (World Health Organization) information, pregnancy hypertension is one of the causes of maternal and infant morbidity and death throughout the world. The novelty in this research is because it examines Literature Review: Factors Associated with Hypertension in Pregnancy. The aim of this research is to determine the factors associated with the occurrence of hypertension in pregnant women. This research method is that the literature is taken from 14 ISSN journals. At the search stage, journals were taken from Elsevier and Google Scholar. The articles were taken from 2018-2023 using the keywords AND hypertension AND pregnancy factors. The results of this research taken from several journals show that the factors related to hypertension in pregnancy are age, while the most dominant factor is age. parity, nulliparity, primipara, preeclampsia, obesity, education, employment, food consumption, and family.